ELECTRON-SOLID INTERACTION - Ariffin, Azian (Universiti Teknologi PETRONAS, 2007)
This final report is intended to be evaluated by the externalexaminerbefore the final presentation is carried out. The report covers all information that has been collected starting from the previous findings until the current stage of the project. The current projectmethodology, discussion and data that have been obtained are also included in this report. The literature review covers the background study of electron-solid interaction. Also, the method used to calculate the probability of interaction between the electron and the intended material is discussed. In addition, the properties of nuclei and findings on Rutherford scattering are added. Molecular geometry and molecular bonding theories is included as to fiirther strengthen the understanding of molecules nature. The projectmethodology covers the methodsthat have been used to conduct research and its relevance with regards to the project, such as collecting information from various resources. The data and discussion will reflect on the formula derived to calculate the probability of interaction. In addition, electrostatic force and energy conservation calculation is done to represent the physics of the interaction between the electron and the material. The structure and properties of selected materials such as Graphite and Silicon is included to be discussed. Finally, the graphical user interface for the simulation is designed using Graphical User Interface Design Environment (GUIDE).